Study of Sb effects on the electrical properties of Ni doped CoSb3 nanostructures - Du, Hongtao. (2009)
This project was designed to investigate the antimony content effect and nickel doping effect on the electrical properties of Ni-doped CoSb3 ( Ni1.25Co2.75Sb12) nanostructures. The purpose was to study the mechanism and to optimize the antimony content in the nanostructure to improve the thermoelectric performance. Ni-doped CoSb3 nanoparticles were synthesized using a modified polyol process with three different initial molar ratio of (Ni + Co) : Sb as 1:4.5, 1:4.75, and 1:5 respectively. Upon successful synthesis and hot pressing of the samples, they were characterized using various techniques. SEM, EDX, and XRD together with the measured electrical parameters obtained from standard four probe testing were analyzed and compared. The results showed that the sample with initial molar ratio of 1:5 has the highest power of 1.84×10-3 W/m K2 at around 458 °C. Nickel doping gave rise to n-type character in the sample and increased the carrier concentration by one order of magnitude. Antimony compensation effect also contributed to an increase in power factor. Electrical properties were improved with the combination of the two parameters.